Education and Human Development: A Conceptual Examination of UNDP and UNESCO Global Reports - Marito Ritonga; Muslim Muslim; Leonardus Teguh Handoyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines how education is conceptually framed within global human development discourse by analyzing major policy texts produced by UNDP and UNESCO. The research is motivated by the growing prominence of education as a multidimensional driver of social transformation, institutional capacity, and sustainable development, alongside persistent theoretical tensions between human capital and capability-based interpretations of learning. Using a non-empirical qualitative design grounded in conceptual and document-based analysis, the study systematically codes and compares global reports to identify recurring normative assumptions, developmental logics, and epistemic models underlying educational narratives. The findings reveal that global reports consistently position education as a translational institution linking agency, governance, equity, and sustainability, while also embedding hybrid conceptual logics that combine economic productivity, social justice, and institutional resilience. This discursive hybridity both enriches and complicates policy interpretation, shaping how development agendas are localized and operationalized across governance levels. The study concludes that education functions as a central epistemic infrastructure of contemporary human development policy, mediating between global norms and institutional practice, and that conceptual analysis of global reports provides critical insight into the governance dynamics of international education discourse.